FUTURE TIME PERSPECTIVE AND LIFE-SPAN - Díaz Morales, Juan Francisco (Anales de Psicología / Annals of Psychology, 2006)
This study described the future temporal perspective (FTP) changes across age. Future time perspective has been evaluated according to Nurmi’s model (1989), which was composed by three components: motivation, planning, and prospective evaluation. The participants were four groups of different ages: 130 adolescents (15-18 years old), 150 undergraduates (19-28 years old), 100 adults middle age (30-59 years old), and 74 elder people (60-88 years old). It has been used the Nurmi’s Goals and Fears Questionnaire, which evaluated each three component through temporal extension, knowledge, realization, planning, control, probability of fu-ture realization, and future affect dimensions. It has been analysed dimensions for goals and fears. The results indicated a U inverted shape in tem-poral distance, progressive increase of knowledge, realization and planning, and decrease of control. Also, the results indicated gender differences according to content of goals and fears.